2004
DOI: 10.1002/hep.20236
|View full text |Cite
|
Sign up to set email alerts
|

Sustained rise of portal pressure after sclerotherapy, but not band ligation, in acute variceal bleeding in cirrhosis

Abstract: During variceal bleeding, several factors may increase portal pressure, which in turn may precipitate further bleeding. This study investigates the early effects of endoscopic injection sclerotherapy (EIS) and endoscopic band ligation (EBL) on hepatic venous pressure gradient (HVPG) during acute bleeding and the possible influence in outcome. In 50 cirrhotic patients with bleeding esophageal varices treated with EIS (n ‫؍‬ 25) or EBL (n ‫؍‬ 25), we performed repeated HVPG measurements before and immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 32 publications
8
92
1
3
Order By: Relevance
“…death. 5 Importantly, in our study, HVPG value after endoscopy was the only independent prognostic factor of failure, highlighting the need for prevention of postendoscopy increase in HVPG. It may be postulated that the presence of blood in the gut or blood volume restitution could affect HVPG.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…death. 5 Importantly, in our study, HVPG value after endoscopy was the only independent prognostic factor of failure, highlighting the need for prevention of postendoscopy increase in HVPG. It may be postulated that the presence of blood in the gut or blood volume restitution could affect HVPG.…”
Section: Discussionmentioning
confidence: 47%
“…of HVPG changes in both groups. 5 Using a two-tailed paired Student's t-test, 16 patients in each arm were required to obtain this effect with an a-error of 0.05 and b-error of 0.8. Categorical data were analysed using the chi-squared test with Yate's correction or Fisher's exact test as appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…62 In addition, one of the studies included in the meta-analysis showed that although HVPG increased significantly immediately after both EVL and sclerotherapy, it remained elevated for the duration of the study (5 days) in the sclerotherapy group while HVPG had decreased to baseline levels by 48 hours after EVL. 104 Therefore, by consensus, EVL is the preferred form of endoscopic therapy for acute esophageal variceal bleeding, although sclerotherapy is recommended in patients in whom EVL is not technically feasible. 7 Combination of pharmacological therapy and endoscopic therapy is the most rational approach in the treatment of acute variceal hemorrhage.…”
Section: D2 Specific Measures To Control Acute Hemorrhage and Prevementioning
confidence: 99%